2009
DOI: 10.1186/1471-2407-9-391
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of angiogenesis by CD105 antigen in epithelial salivary gland neoplasms with diverse metastatic behavior

Abstract: BackgroundInformation on the biology of metastasis development in salivary gland tumors is scarce. Since angiogenesis seems associated with this phenomenon in other tumors, we sought to compare salivary gland tumors with diverse metastatic behavior in order to improve the knowledge and management of these lesions.MethodsSamples from the most important salivary gland tumors were segregated according to its metastatic behavior and submitted to routine immunohistochemistry to identify vessels positive for CD105 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 23 publications
(29 reference statements)
5
33
2
Order By: Relevance
“…In the study conducted by Cardoso and others, which was similar to our study, it was detected that there is a higher increase in development of blood vessels within the malignant tumors compared to benign tumors (Cardoso et al, 2009).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In the study conducted by Cardoso and others, which was similar to our study, it was detected that there is a higher increase in development of blood vessels within the malignant tumors compared to benign tumors (Cardoso et al, 2009).…”
Section: Discussionsupporting
confidence: 90%
“…In the same study conducted by Costa and Cardoso, it was evidenced that there is an increased incidence of blood vessel in MEC compared to ACC (Costa et al, 2008;Cardoso et al, 2009).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…These findings are in line with previous observations of (Cardoso et al, 2009 andMoghadam et al, 2015) who reported that salivary gland carcinomas demonstrated higher increase in the formation of blood vessels than benign tumors. Thus, the present and the previous findings prove that the development of new blood vessels is essential for clonal expansion which reflects higher rate of neovascularization and invasiveness of malignant SGTs (Sharma et al, 2005).…”
Section: Results:-supporting
confidence: 93%
“…Discussion:-Malignant SGTs constitute a major challenge in head and neck oncology because of its low frequency, variation in histological types, difficult surgical approach and poor response to therapy. Therefore, the present study was conducted to evaluate the quantification of angiogenesis in SGTs by measuring the MVD, since it is considered as an important prognostic factor which significantly associates with overall survival and correlates with the grades of malignancy (Cardoso et al, 2009). …”
Section: Results:-mentioning
confidence: 99%